Advances in the study of Ophiopogon japonicus polysaccharides: structural characterization, bioactivity and gut microbiota modulation regulation - Li, Jiani; Zhou, LiQuan; Xiao, ZuoWei (Frontiers in Pharmacology, 2025)
Ophiopogon japonicus polysaccharides (OJPS), the principal bioactive constituents isolated from Ophiopogon japonicus, demonstrate substantial physiological efficacy. OJPS is characterized by a high molecular weight, typically ranging from 2.48 to 324.7 kDa. Emerging evidence indicates that OJPS modulates the composition and structural organization of the gut microbiota, thereby maintaining intestinal barrier integrity and enhancing both gastrointestinal and systemic homeostasis. Moreover, OJPS and its metabolic derivatives engage in dynamic interactions with microbial communities, mediating cellular signaling cascades and endocrine regulation to elicit hypoglycemic effects. Despite these findings, comprehensive analyses of OJPS extraction and purification methodologies, structural elucidation, biological functionalities, and mechanistic insights into its crosstalk with the gut microbiota remain scarce. This review systematically synthesizes contemporary knowledge pertaining to the preparation, structural attributes, bioactivity, and mechanistic underpinnings of OJPS, with particular emphasis on its dual regulatory role in host physiology and gut microbial ecology.